Boundedness for a Class of Generalized Commutators of Fractional Hardy Operators with a Rough Kernel - Xiao Yu; Shanzhen Lu (Abstract and Applied Analysis)
The authors consider the generalized commutator of fractional Hardy operator with a rough kernel as follows: where , , and with . The authors prove that is bounded on Herz type space and -Central Morrey space with , which is an open problem for .